Enhanced 3D Seismic Image Resolution by Applied Attributes for Improved Carbonate Reservoir Characterization in Karawang Region, North West Java - Sudarsana, Muhammad Rizki; Syafri, Ildrem; Agus Nur, Andi; Abdurrokhim, Abdurrokhim (Indonesian Journal on Geoscience, 2025)
The study focuses on the enhancement of 3D seismic data to improve the interpretation of carbonate growth phases within Middle Miocene limestone formations in the Karawang region, north west Java. By applying a sequential workflow of various seismic attributes, including the second derivative, phase shift, frequency filter, structural smoothing, and iterative trace Automatic Gain Control (AGC), the vertical resolution of seismic events is significantly improved, from an initial dominant frequency of 22 Hz (38 m tuning thickness) to a final effective dominant frequency of 33 Hz after all enhancements. These enhancements facilitate a clearer delineation of stratigraphy, depositional patterns, and the geometry of carbonate growth cycles. The integration of well data, including wireline logs and synthetic seismograms, with enhanced 3D seismic sections provides a comprehensive understanding of subsurface features and porosity development in the target area. The enhanced data enabled the identification of four distinct carbonate growth phases, revealing complex thickness variations and depositional architectures controlled by sea-level fluctuations. This integrated approach demonstrates the critical role of optimized seismic attribute application for detailed carbonate reservoir characterization and optimizing well placement for hydrocarbon exploration and exploitation.